TRENDS AND CORRELATIONS IN ROMANIA'S AGRO-FOOD FOREIGN TRADE IN THE PERIOD 2007-2016 - Agatha POPESCU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The purpose of the paper was to analyze the trends and correlations in Romania's agro-food trade in the period 2007- 2016 based on the data supplied by the National Institute of Statistics. The statistical parameters of mean, standard deviation, coefficient of variation, growth rate, trend line, regression model, Pearson correlation coefficient have been used in this study. The export value of agro-food products reached Euro 6.06 billion, while the import value of agro-food products accounted for Euro 6.78 billion in the year 2016. Despite that both export and import value increased, Romania is still a net exporting country. The year 2013 and 2014 registered a positive trade balance. The economic efficiency in Romania's agro-food foreign trade has increased. This was proved by the growth of the share of the agro-food products export in Romania's export value, and by the share of export value in the GDP carried out in agriculture as well as in terms of export/import coverage rate. Romanian producers must continue to pay a special attention to the factors stimulating the growth of the agricultural production and improve the quality of agro-food products in order to cover better the requirements of the domestic and also of the international market, leading to a positive trade balance.